2017
DOI: 10.1155/2017/7517450
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use as a Strong Predictor of Poor Academic Achievement among University Students

Abstract: Background Substance use is a growing concern globally and its association with students' academic performance is not well studied. Objective This study was aimed to assess the prevalence of substance use (alcohol, tobacco, and khat) and its association with academic performance among university students. Methods Cross-sectional study was conducted among Wolaita Sodo University students. A total of 747 students were selected by using cluster sampling technique. Data were collected by pretested self-administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 25 publications
5
60
0
1
Order By: Relevance
“…expenses related to cigarette use, and possible long-term addiction. e ill effects of smoking if addressed early with effective educational and campus support activities can reduce cigarette smoking and create a culture that does not condone use in campus facilities and community spaces [33]. Special attention should be given to universities when implementing the policies and interventions to reduce cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…expenses related to cigarette use, and possible long-term addiction. e ill effects of smoking if addressed early with effective educational and campus support activities can reduce cigarette smoking and create a culture that does not condone use in campus facilities and community spaces [33]. Special attention should be given to universities when implementing the policies and interventions to reduce cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 7,861 study participants were included from 13 studies. ese studies were carried out from January 2011 to December 2018 from 10 different universities in seven regions of the country: Addis Ababa � 1, Amhara � 3, Dire Dawa � 1, Oromia � 1, Somali � 2, SNNPR � 3, and Tigray � 1 [22][23][24][25][26][27][28][29][30][31][32][33][34]. All of the studies included were cross-sectional with a sample size ranging from 271 to 1022 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We did not find an association of ISU prevalence or the extent of ISU with the average grade in college, nor the self‐reported development of study performance. Other studies even report lower academic performance and higher college dropout rates of students using illicit substances (Rimsza & Moses, ; Martins & Alexandre, ; Arria et al ., ; Bajwa et al ., ; Meshesha et al ., ; Mekonen et al ., ). The fact that we did not find associations between our measurement of present ISU (defined as the number of illicit substances consumed in the past month) and low academic performance may be explained by the nature of the measurement which does not include the dosage or frequency of illicit substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Illicit substance use among students has shown to be associated with a higher college dropout rate, lower academic performance and higher rate of unemployment after receiving a college degree (Rimsza & Moses, 2005;Martins & Alexandre, 2009;Arria et al, 2013;Bajwa et al, 2013;Meshesha et al, 2015;Mekonen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, no improvement in scores was observed when age-group wise analysis was done among 'ever-users'. The possibility of less attentive attitude of students or a state of denial cannot be ignored among this group, as there were reports of mental distress being a factor for less academic performance among students with substance use (Mekonen et al, 2017;Dessie et al, 2013). Moreover, financial hardships, familial influence and psycho-social influence could also lead to poor academic performance (Abdu-Raheem, 2013).…”
Section: Discussionmentioning
confidence: 97%